Vertebral augmentation the comprehensive guide to vertebroplasty, kyphoplasty, and implant augmentation - Beall, Douglas P. (Thieme Society of Interventional Radiology, 2020)
"Vertebral compression fractures (VCFs) result from trauma or pathologic weakening of the bone and are associated with conditions such as osteoporosis or malignancy. Worldwide, VCFs impact one in three women and one in eight men aged 50 and older, with more than 8.9 million fractures incurred annually. Copublished by Thieme and the Society of Interventional Radiology, Vertebral Augmentation: The Comprehensive Guide to Vertebroplasty, Kyphoplasty, and Implant Augmentation provides a practical, clinical discussion of these minimally invasive spine interventions"--